ANALISIS PERAN BIOTEKNOLOGI REKAYASA GENETIKA UNTUK PENINGKATAN KUALITAS PADA TOMAT DAN KENTANG - Endah Rita Sulistya Dewi; Atip Nurwahyunani, Khusna Y Habsari, Elsa Septiani R Miharjo, Ema Auliatuzahra, Kamila N Afifah, Mer (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Most of the engineering or modification of plant traits is carried out to address the increasing global food needs with high quality. The growing demand for potatoes and tomatoes has led to a high market demand for high-quality tomato and potato plants, necessitating the sale of quality plants. Therefore, continuous efforts are made to improve the quality in the tomato and potato farming sector. This is aimed at producing new plants with superior characteristics compared to previous ones. This research uses a literature study from 15 journal articles from 2015-2023 related to the development and application of biotechnology in agriculture for the production of fertilizers to increase crop yields. The literature was searched using Google Scholar with the keywords 'genetic engineering utilization in tomato fruit' and 'genetic engineering utilization in potatoes.' The analysis was conducted using descriptive analytics, and the data were examined narratively descriptively. The results of the discussion on the use of genetic engineering in tomato and potato plants show that the production of tomato plant seeds has significantly increased. This can include an increase in the number of fruits produced per plant or an increase in fruit size. The role of biotechnology in the utilization of genetic engineering in tomato and potato plants can be considered a solution because it has a significant impact on plant growth and agricultural yields..